2010
DOI: 10.1021/cg101162a
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Forms of β-Resorcylic Acid: How Exhaustive Should a Polymorph Screen Be?

Abstract: A combined experimental and computational study was undertaken to establish the solid-state forms of β-resorcylic acid (2,4-dihydroxybenzoic acid). The experimental search resulted in nine crystalline forms: two concomitantly crystallizing polymorphs, five novel solvates (with acetic acid, dimethyl sulfoxide, 1,4-dioxane, and two with N,N-dimethyl formamide), in addition to the known hemihydrate and a new monohydrate. Form II°, the thermodynamically stable polymorph at room temperature, was found to be the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 64 publications
2
68
0
Order By: Relevance
“…The distinct steps and hysteresis between the sorption and desorption isotherms are characteristic of a stoichiometric hydrate. 14,77,78 …”
Section: Resultsmentioning
confidence: 99%
“…The distinct steps and hysteresis between the sorption and desorption isotherms are characteristic of a stoichiometric hydrate. 14,77,78 …”
Section: Resultsmentioning
confidence: 99%
“…1). The structures of the parent -resorcylic acid (Parkin et al, 2007; measured at 90, 100, 110 and 150 K) and of its hemihydrate (Horneffer et al, 1999;Braun et al, 2011) have been reported previously. The molecular geometry of (I) is in good agreement with these reported structures.…”
Section: Resultsmentioning
confidence: 61%
“…2. For a detailed assignment of the peaks, dedicated paper are available [10,11]. Presumably, the short time of reaction and the low temperatures, hindered the formation of the g-isomer, and the IR spectra show only the b-resorcylic acid signals.…”
Section: Batch Experiments Of Co 2 Absorption In a Parr Reactor Undermentioning
confidence: 99%